Code Mixing on Livjunkie’s YouTube Content: A Socio-linguistic Analysis - Kirana, Vanessa Enxi; Masykuroh, Qanitah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study was conducted to analyse the use of code-mixing in Livjunkie’s YouTube content focusing on the types of code-mixing and the factors un-derlying their use. Methodology: Under the umbrella of qualitative research, the data are the utterances of Livjunkie, a popular Indonesian beauty vlogger, which contain code-mixing collected using documentation. The data are then analysed referring to Muysken (2000) for the types of code mixing and Holmes (2017) for the factors influencing code mixing. Results: The study revealed that insertion was the most common type of code mixing (61.8%), followed by congruent lexicalization (21.8%) and alternation (12.7%). Furthermore, three main factors influencing code-mixing were identified i.e. recipient identity (53.33%), social relationship (28.57%), and topic change (35.71%). Applications/Originality/Value: The frequent use of code-mixing highlights the informal and engaging nature of Livjunkie’s content, which aims to connect more personally with its di-verse audience. This research contributes to understanding the role of code-mixing in digital content and offers insights into how multilingual creators like Livjunkie effectively use the strategy to increase audience engagement and cultural representation while navigating global and local language dy-namics.